(untitled) (Revista Iberoamericana de Bioética, 2019)
The last decades have witnessed a search for true inclusion in education, especially considering that inclusive education refers to an education based on the needs of each individual. This has been even more difficult in the area of Sciences in universities, which has high enrollment figures with students seeking to develop scientific skills. This makes it more difficult to provide individualized attention in the process of generating productive persons with social responsibility. It is therefore necessary to look for strategies of inclusion that will help them to achieve this goal.